Konflik Interpersonal dan Iklim Organisasi terhadap Komitmen Afektif Organisasi Karyawan - Rahmi; Latipun; Tulus Winarsunu (Psyche 165 Journal, 2022)
Employee commitment is one of the keys that determine the success of an organization to achieve its goals.Employees who have a commitment to the organization usually show a caring attitude to their duties, they are very responsible for carrying out tasks and very loyal to the company. Organizational commitment especially affective commitment as one of the factors in human resources. Factors suspected to affect affective commitment is interpersonal conflict and organizational climate. This study was conducted to see the effect of interpersonal conflict and organizational climate on affective commitment. This study uses a quantitative research. The population in this study are employees of PT. Semen Padang. the Subjects are 128 employees using incidental sampling technique. Collecting data using the instrument in the form of scale, the scale of interpersonal conflicts, organizational climate scale and affective commitment scale. Data analysis technique used in this research is regression analysis. The results showed there is no effect between interpersonal conflict on affective commitment to employees (β = 0095, p = 0493), then there is significant effect between organizational climate on affective commitment (β = 0.279, p = 0.000) effective contribution of the organization's climate to affective commitment of 8.2%, and there is influence between conflict interpersonal and organizational climate on affective commitment (F = 7706, p = 0.001), Effective contribution of interpersonal conflict and organizational climate to affective commitment by 11%.